Catalytic Formation of Cyclic Carbonates using Gallium Aminotrisphenolate Compounds and Comparison to their Aluminium Congeners: A Combined Experimental and Computational Study. Issue 19 (19th August 2021) - Álvarez‐Miguel, Lucía; Burgoa, Jesús Damián; Mosquera, Marta E. G.; Hamilton, Alex; Whiteoak, Christopher J.
Abstract: This work reports on the use of gallium aminotrisphenolate compounds as catalysts for the synthesis of cyclic carbonates from epoxides and CO2 . The results show that they are highly active, and more so than the corresponding aluminium congeners. The catalyst system is applicable at low and elevated temperatures across a wide substrate scope including terminal, internal, multiple and fully deuterated epoxides. Applying low catalyst loadings has allowed for a TON of 344, 000 to be obtained, highlighting their stability. A DFT investigation has confirmed that the gallium catalysts have lower energetic profiles compared to the aluminium congeners. Measurement of the Lewis acidity of both the gallium and aluminium aminotrisphenolate compounds using the Gutmann‐Beckett method provides the experimental proof that the gallium compounds are more Lewis acidic than their aluminium congeners. Finally, Ab‐Initio Molecular Dynamic (AIMD) simulations have investigated and quantified the dynamic behaviour of the catalytic systems, highlighting an important increase in fluxionality in some cases which helps to explain the increase in catalytic activity. Abstract : Computational study : A highly active catalyst system based on gallium has been developed for the conversion of CO2 and epoxides to cyclic carbonates. The catalyst displays wide substrate scope and is operative at both ambient and elevated temperatures. DFT and Ab‐Initio Molecular Dynamic studies compliment the experimental work and provide key information as to why the gallium compounds are more active than their aluminium congeners.